Fish consumption and multiple health outcomes: Umbrella review. (May 2020) - Li, Ni; Wu, Xiaoting; Zhuang, Wen; Xia, Lin; Chen, Yi; Wu, Chuncheng; Rao, Zhiyong; Du, Liang; Zhao, Rui; Yi, Mengshi; Wan, Qianyi; Zhou, Yong
Abstract: Background: Fish contains a variety of essential nutrients, which may contribute to multiple health benefits in humans. Conversely, it also may contain contaminants, resulting in confusion over the health impact of fish consumption. Scope and approach: To assess the strength and validity of associations between fish intake and multiple health outcomes. We performed an umbrella review of systematic reviews and meta-analyses in humans. Key findings and conclusions: Of the 55 unique outcomes in the identified 89 systematic reviews and meta-analyses, fish consumption did more benefit than harm for a variety of health outcomes with largest risk reduction at 2 to 4 servings per week. Dose-response analyses revealed that every 20 g/d (approximately one serving/week) increment could decrease 2%–7% risk of coronary heart disease mortality, cardiovascular disease mortality, all-cause mortality, stroke, myocardial infarction, acute coronary syndrome, heart failure, gastrointestinal cancer, metabolic syndrome, dementia and Alzheimer's disease. Beneficial associations were also found for cancers, atopic, musculoskeletal, gastrointestinal and ophthalmologic outcomes. Caution is warranted for potential allergy or contamination when advising during pregnancy and young children. Fish intake appears generally safe in this umbrella review with largest risk reduction for a range of health outcomes at two to four servings per week, and seems more beneficial than harmful. High-quality prospective studies are needed. Graphical abstract: Image 1 Highlights: Umbrella review of 55 outcomes in 89 systematic reviews and meta-analyses. Fish intake reduces all-cause mortality, CVD, cancer and other outcomes. Fish intake looks generally safe with largest risk reduction at 2–4 servings/week. Every 20 g/d increment could decrease 2%–7% risk of various health outcomes. Caution is warranted for potential allergy or contamination.